The Effect of Aerobic Exercise on VO2max in Physiotherapy Students at Surakarta Polytechnic - Utomo, Budi; Kusumawati, Yoni Rustiana (Poltekkes Kemenkes Surakarta, 2025)
Background: Aerobic exercise is a physical fitness exercise that can increase VO2 max. The provision of this exercise is intended to provide exercise on the increase in aerobic physical exercise by measuring maximum oxygen consumption. An indicator of physical fitness, and heart and lung endurance is VO2max. VO2max denotes the peak amount of oxygen the body can absorb and use during vigorous exercise before reaching fatigue. The purpose of this study was to determine the effect of aerobic exercise on VO2 max in Physiotherapy as a student at Surakarta Polytechnic. Methods: This research is a quasi-experimental study with a one-group pre-test and post-test design. A total of 56 students were selected using simple random sampling and received treatment with aerobic exercise in the form of 30-minute walking sessions, three times a week, for 12 sessions. Data analysis to determine the difference between pre-and post-tests was conducted using the Wilcoxon test. Results: The results of this study indicate that aerobic exercise can increase VO2max in Physiotherapy students at Surakarta Polytechnic, as shown by the six-minute walking test. The hypothesis test yielded a p-value of <0.001, indicating a statistically significant difference, with a mean increase of 6.44 in VO2max values. Conclusion: There is a different effect between before and after treatment given aerobic exercise can increase VO2 max in Physiotherapy students at Surakarta Polytechnic. Regular aerobic exercise is recommended to be incorporated into students' routines to improve cardiovascular endurance and support physical fitness.